2009
DOI: 10.1200/jco.2009.21.8909
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial of Four Cisplatin-Containing Doublet Combinations in Stage IVB, Recurrent, or Persistent Cervical Carcinoma: A Gynecologic Oncology Group Study

Abstract: A B S T R A C T PurposeAssess toxicity and efficacy of cisplatin (Cis) doublet combinations in advanced and recurrent cervical carcinoma. Patients and MethodsPatients were randomly assigned to paclitaxel 135 mg/m 2 over 24 hours plus Cis 50 mg/m 2 day 2 every 3 weeks (PC, reference arm); vinorelbine 30 mg/m 2 days 1 and 8 plus Cis 50 mg/m 2 day 1 every 3 weeks (VC); gemcitabine 1,000 mg/m 2 day 1 and 8 plus Cis 50 mg/m 2 day 1 every 3 weeks (GC); or topotecan 0.75 mg/m 2 days 1, 2, and 3 plus Cis 50 mg/m 2 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
424
4
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 616 publications
(450 citation statements)
references
References 19 publications
4
424
4
18
Order By: Relevance
“…3,4 Since the publication of the initial studies examining cisplatin in the treatment of cervical cancer, a number of effective single-agent and combination drug regimens have been identified that exhibited improved response rates, without a significant effect on overall survival. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The poor oncologic outcome in this patient population represents an unmet clinical need and has driven the exploration of new treatment paradigms. 3 Most recently, the results of Gynecologic Oncology Group (GOG) protocol 240 were presented and Scan the QR Code with your phone to obtain FREE ACCESS to the articles featured in the Clinical Therapeutics topical updates or text GS2C65 to 64842.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Since the publication of the initial studies examining cisplatin in the treatment of cervical cancer, a number of effective single-agent and combination drug regimens have been identified that exhibited improved response rates, without a significant effect on overall survival. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The poor oncologic outcome in this patient population represents an unmet clinical need and has driven the exploration of new treatment paradigms. 3 Most recently, the results of Gynecologic Oncology Group (GOG) protocol 240 were presented and Scan the QR Code with your phone to obtain FREE ACCESS to the articles featured in the Clinical Therapeutics topical updates or text GS2C65 to 64842.…”
Section: Introductionmentioning
confidence: 99%
“…Monk et al recently reported results from the largest and most complex randomized, multicenter phase III clinical trial performed in this population. 24 In this 4-arm trial, none of the experimental regimens was found to be superior to the control arm of cisplatin plus paclitaxel. The RRs for the control, cisplatin plus vinorelbine, cisplatin plus gemcitabine, and cisplatin plus topotecan were 29.1%, 25.9%, 22.3%, and 23.4%, respectively.…”
Section: Clinical Ovarian Cancer December 2011mentioning
confidence: 99%
“…20, 24 Moore et al reported that, with the exception of select hematologic toxicities (eg, grade 3/4 neutropenia and anemia), the doublet was well tolerated, with all nonhematologic grade 3/4 toxicities and grade 3/4 thrombocytopenia occurring in Ͻ 10% of the subjects. 20 Similarly, Monk et al observed that grade 3/4 hematologic toxicities occurred more frequently in patients receiving the cisplatin/topotecan doublet than among patients treated with cisplatin plus paclitaxel (anemia, 34.9% vs. 16.8%; neutropenia, 82.6% vs. 78.2%; and thrombocytopenia, 34.9% vs. 6.9%, respectively).…”
Section: Clinical Ovarian Cancer December 2011mentioning
confidence: 99%
See 2 more Smart Citations